Technology in Organizations and Its Detriments - Valimohamadi, Somayeh; Rahmati, Mohammad Hossein; Shafiee Roodposhti , Meysam (AI and Tech in Behavioral and Social Sciences, 2024)
Many small and medium-sized businesses commit themselves economically to adopting technologies to avoid organizational decline. They must do this by paying attention to the inherent risks of these technologies and ensuring the security of their business continuity, even after unexpected and challenging events. Accordingly, the aim of the present study is to examine technology in organizations and its detriments. The research method is descriptive-analytical and utilizes library resources. Pathology based on information to analyze and accurately understand the technology required by the organization, management styles, and other problem-solving system elements is necessary. In other words, pathology, diagnosing the problem, and its scientific focus to determine the necessary actions to improve organizational performance is essential. This research attempts to identify the criteria and indicators of structural pathology in organizations and to classify these detriments in the technological branch. Successful technology-based organizations, through supporting intellectual property rights, possess extensive assets; therefore, keeping pace with technological changes is of fundamental importance. Expert research in identifying technological detriments significantly contributes to reducing organizational technology deficiencies.